Determinants of Hydroxychloroquine Blood Concentration Variations in Systemic Lupus Erythematosus. Issue 8 (28th July 2015) - Jallouli, M.; Galicier, L.; Zahr, N.; Aumaître, O.; Francès, C.; Le Guern, V.; Lioté, F.; Smail, A.; Limal, N.; Perard, L.; Desmurs‐Clavel, H.; Le Thi Huong, D.; et al.
<x xml:space="preserve">Abstract</x> Objective Blood concentrations of hydroxychloroquine (HCQ) vary widely among patients with systemic lupus erythematosus (SLE). A pharmacokinetic/pharmacodynamic relationship has been found in different situations, and a very low blood concentration of HCQ is a simple marker of nonadherence to treatment. Therefore, interest in blood HCQ concentration measurement has increased, but little is known about factors that influence blood HCQ concentration variability. This study was undertaken to analyze determinants of blood HCQ concentrations. Methods We conducted a retrospective analysis of patient data, including data from the Plaquenil Lupus Systemic (PLUS) study, to determine the association of epidemiologic, clinical, and biologic factors with blood HCQ concentrations. Data for nonadherent patients (blood HCQ concentration <200 ng/ml) were excluded. Results To examine homogeneous pharmacologic data, we restricted the analyses of the PLUS data to the 509 SLE patients receiving 400 mg/day. We found no association of ethnicity or smoking with blood HCQ concentrations and no pharmacokinetic drug–drug interaction with antacids or with inhibitors or inducers of cytochrome P450 enzymes. On multivariate analysis, high body mass index (P = 0.008), no treatment with corticosteroids (P = 0.04), increased time between the last tablet intake and measurement of blood HCQ concentrations (P = 0.017), low platelet count (P < 0.001), low neutrophil count (P < 0.001), and high estimated creatinine clearance (P < 0.001) were associated with low blood HCQ concentrations. In 22 SLE patients with chronic renal insufficiency (median serum creatinine clearance 52 ml/minute [range 23–58 ml/minute]) who received 400 mg/day HCQ, the median blood HCQ concentration was significantly higher than that in the 509 patients from the PLUS study (1, 338 ng/ml [range 504–2, 229 ng/ml] versus 917 ng/ml [range 208–3316 ng/ml]) (P < 0.001). Conclusion We provide a comprehensive analysis of determinants of blood HCQ concentrations. Because this measurement is increasingly being used, these data might be useful for clinicians.